2016
DOI: 10.1088/0031-9155/61/13/4796
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided detection of prostate cancer in T2-weighted MRI within the peripheral zone

Abstract: In this paper we propose a prostate cancer computer-aided diagnosis (CAD) system and suggest a set of discriminant texture descriptors extracted from T2-weighted MRI data which can be used as a good basis for a multimodality system. For this purpose, 215 texture descriptors were extracted and eleven different classifiers were employed to achieve the best possible results. The proposed method was tested based on 418 T2-weighted MR images taken from 45 patients and evaluated using 9-fold cross validation with fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
3

Relationship

6
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 82 publications
(233 reference statements)
0
30
0
Order By: Relevance
“…The machine learning algorithms employed in this study are the Random Forest (RF), Multilayer Perceptron (MLP), Logistic Regression (LR), Naïve Bayes (NB), Bayesian Network (BNet), k-Nearest Neighbours (k-NN), C4.5 (J48), Alternate Decision Tree (ADTree), Logistic Model Trees (LMT), AdaBoostM1 (AdaBoost) and Support Vector Machine (SVM). Following our previous studies, 19,20 we used the CVParame-terSelection and GridSearch techniques to select associated hyper-parameters for each classifier (available in the WEKA data mining suite).…”
Section: Machine Learning Algorithmsmentioning
confidence: 99%
“…The machine learning algorithms employed in this study are the Random Forest (RF), Multilayer Perceptron (MLP), Logistic Regression (LR), Naïve Bayes (NB), Bayesian Network (BNet), k-Nearest Neighbours (k-NN), C4.5 (J48), Alternate Decision Tree (ADTree), Logistic Model Trees (LMT), AdaBoostM1 (AdaBoost) and Support Vector Machine (SVM). Following our previous studies, 19,20 we used the CVParame-terSelection and GridSearch techniques to select associated hyper-parameters for each classifier (available in the WEKA data mining suite).…”
Section: Machine Learning Algorithmsmentioning
confidence: 99%
“…This suggests that using a combination of medium sizes of R captures more discriminant features regardless of the topology. Previous studies [37][38][39] on texture descriptors across different window sizes found that using a small value of R does not capture sufficient information about the regions due to the limited intensities and grey level variations. On the other hand, using a large R tends to alter the actual representation of the area, especially when one class dominates over another class.…”
Section: Results On Different Multiresolutionsmentioning
confidence: 99%
“…Combining prediction results of several classifiers is a common approach in machine learning [26], [27]. The main advantage of this approach is that it prevents a single model from being exploited by outliers/noise/complicated cases.…”
Section: Discussionmentioning
confidence: 99%